Smartphone apps for tracking physical activity and sedentary behavior: A criterion validity review - Raul Cosme Ramos Prado; Margarethe Thaisi Garro Knebel; Evelyn Helena Corgosinho Ribeiro; Inaian Pignatti Teixeira; Jeffer Eidi Sasaki; Luciano Vieira de Araújo; Paulo Henrique Guerra; Alex Antonio Florindo (Revista Brasileira de Atividade Física e Saúde)
Smartphone apps have been developed and investigated in validation studies for tracking human behavior such as physical activity (PA) and sedentary behavior (SB). However, as it is unclear whether these apps are valid for tracking PA and SB when compared to research-grade accelerometers, thus, this systematic review aimed to investigate the validity of smartphone apps for tracking PA and SB using the accelerometer as a criterion measure. A systematic search was conducted in PubMed, Web of Science, SportDiscus, and Scopus databases. The mean percentage difference (MPD) was used to evaluate criterion validity. Ten studies (n = 662) validating different apps using ActiGraph accelerometers as criteria measure (six were conducted in free-living conditions, two in laboratory conditions, and two in both conditions) were included for analyses. While four apps were considered valid for tracking PA, six were not valid or fully valid. The MPD analysis revealed that apps provide no valid scores for tracking PA measures (MPD = -12.6 – 37.7). The scarcity of studies investigating SB limits the tracking of the results on this behavior. Study designs, smartphone location, and exercise intensity tend to affect the accuracy of apps tracking PA; thus, the current review showed conflicting results among studies. This review shows that it is not possible to generalize the valid scores for all apps.